Development of Inland Aquaculture in India, with special reference to Hypophysation Technology - Bhowmick, Rai Milan (Journal of the Inland Fisheries Society of India, 2019)
Fish husbandry has emerged as a major source of animal protein for the expanding human population in the world. Fish not only provides nutrition but also resists some diseases. In India population is in the increase. It is estimated that by 2020 AD population will reach at 1.4 billion (P.Kumar,2000) increasing the gap between the demand and supply of fish.Inland aquaculture which is a major contributor in fish production in inland sector is extended throughout the country even in the interior region of the rural sector. To reduce the gap between demand and supply the country has to rely on aquaculture which is indicating increasing trend in fish production. Fish culture is an age old practice